Depression and suicide in nursing students and the teaching knowledge about this suffering (Research, Society and Development, 2020)
Introduction: This stud intends to approach the historic of depression and suicide among nursery students and the professional knowledge about these diseases. Depression constitutes itself as a mental suffering and implies in a negative way in the learning process of the students and, besides that, increases the suicide possibility between students with serious levels of depression. Objective: Carry out a bibliographic data survey about the historic of depression and suicide between nursery students and evaluate professor's knowledge and interventions when dealing with this mental suffering. Method: It is a integrative review. Firstly, was formulated the guiding question: "What says the literature about the historic of depression and suicidal ideations between nursery students and which are professor's interventions when dealing with these problems?". Was made surveys in the following data bases: Data bases in nursery, Latin-American and Caribbean literature in Health Science, Portal Capes and Pubmed. After that, was prepared an article's overview with the purpose of synthetize the main relevant informations of these stud. Results and Conclusion: Was observed 20 articles related to the historic of these mental sufferings between nursery students. There are findings that mention both depression and suicide resulted from serious levels of depression. Other data highlights the association of stress and depression symptoms. Few studs mention about professor's interventions when dealing with these problems.